Long-term outcomes and quality of life following parotidectomy for benign disease: head and neck = Risultati a lungo termine e qualità della vita dopo parotidectomia per patologie benigne - Plath, Michaela; Sand, Matthias; Cavaliere, Carlo; Plinkert, Peter K.; Baumann, Ingo; Plath, Karim (Acta otorhinolaryngologica italica, 2022)
Objective. Parotidectomy worsens quality of life (QoL) in the short-term, but the long-term impact is unknown. In this study, we analysed the long-term effects of parotidectomy on QoL. Methods. In this prospective long-term follow-up study, participants were divided into three groups: short-term (ST) follow-up of six weeks, long-term (LT) follow-up of 13 years and short-and long-term (SLT) follow-up. QoL was assessed using the Parotidectomy Out-come Inventory (POI-8). Parotidectomies were classified based on whether the great auricu-lar nerve (GAN) had been preserved or sacrificed. Results. In total, 164 observations were analysed, 74 in the LT group, 57 in the ST group and 33 in the SLT group. Hypoaesthesia was a major problem and facial palsy was a minor problem. Pain (p < 0.01) and hypoaesthesia (p < 0.001) were significantly lower after 13 years compared with after six weeks, and QoL was higher after 13 years compared with after six weeks (p = 0.04). The disease-specific impairment rate decreased from 70% at short-term follow-up to 30% at long-term follow-up. Removal of the GAN was associated with hypoaesthesia in the ST group (p = 0.028). Conclusions. Hypoaesthesia has a long-term impact on the QoL, and this should be empha-sised during preoperative discussions.
Veröffentlich am 30.06.2022
Gesehen am 11.10.2022